2018
DOI: 10.21608/ejnf.2018.75768
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Rumen-Protected Lysine (Hydroxy Methyl Lysine) Supplementation on Performance and Blood Metabolites in Barki Sheep

Abstract: ffect of rumen-protected lysine in the form of Hydroxyl methyl lysine (HML) on average daily gain (ADG), dry matter intake (DMI), nutrient digestibility, nitrogen balance blood metabolites, were evaluated in two experiments using growing Barki lambs. In first experiment, fifteen lambs were housed individually and assigned into three equal groups fed on basal diet (no lysine-control), free lysine (positive control, F-LYS) and protected lysine (P-LYS) equivalent to 3 g/d of lysine. The experiment lasted for 10 w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
1
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 14 publications
2
1
0
Order By: Relevance
“…The means of cholesterol, triglyceride, ALT and AST concentration were (87.00, 76.28, 85.40, 88.52) mg / 100 ml, and (63.49, 57.98, 60.11, 62.99) mg / 100 mL and ALT (14.64,15.51,16.91,14.84) IU / L, AST (40.71,42.22,43.37,41.33) IU / L, respectively. The results were in agreement with the results of Mousavi et al (2016) and Elwakeel et al (2018) when adding amino acids (methionine and lysine) to the diets of Iranian ewes and lambs of the Egyptian Barqi breed, which they did not recorded significant differences in the concentration of triglyceride and cholesterol. Whereas, it did not agree with the results of Rodriguez-Guerrero et al (2018) when using protected methionine amino acid, which reported significant differences in cholesterol and triglyceride concentrations.…”
Section: S Ns Significantsupporting
confidence: 92%
See 1 more Smart Citation
“…The means of cholesterol, triglyceride, ALT and AST concentration were (87.00, 76.28, 85.40, 88.52) mg / 100 ml, and (63.49, 57.98, 60.11, 62.99) mg / 100 mL and ALT (14.64,15.51,16.91,14.84) IU / L, AST (40.71,42.22,43.37,41.33) IU / L, respectively. The results were in agreement with the results of Mousavi et al (2016) and Elwakeel et al (2018) when adding amino acids (methionine and lysine) to the diets of Iranian ewes and lambs of the Egyptian Barqi breed, which they did not recorded significant differences in the concentration of triglyceride and cholesterol. Whereas, it did not agree with the results of Rodriguez-Guerrero et al (2018) when using protected methionine amino acid, which reported significant differences in cholesterol and triglyceride concentrations.…”
Section: S Ns Significantsupporting
confidence: 92%
“…Different small letter within column means significant difference (*) (p<0.05) between groups. Table (6) shows that there are significant differences (p <0.05) in the concentration of albumin in the fourth group, which recorded (3.81) g / 100 ml compared with the control group, reaching (3.20) g / 100 ml, may be due to increasing the absorption of the true protein in the small intestine when feeding the protected protein (Oh et al, 2008), and this is similar to the results of Gavade et a., (2019), that confirmed that a significant difference was obtained in albumin concentration when feeding calves on a mixture of the protected amino acids methionine and lysine (3 + 20 g / animal / day) when compared with the control group, whereas, it is different from the results of Elwakeel et a., (2018), which did not record significant differences in the albumin concentration compared to the control group when they added the protected amino acid lysine at (3) g / animal / day to the diets of lambs of the Egyptian Barqi breed. A significant (p <0.05) increase was observed in glucose concentration in the fourth and second groups, reaching (69.11, 68.43) mg / 100 ml, respectively, compared to the control group, reaching (43.85) mg / 100 ml, and the reason may be due to the metabolism of the amino acid methionine in the liver and its association with an increase in glucose concentration (Ganong, 2005;Sun et a., 2016) .…”
Section: S Ns Significantsupporting
confidence: 89%
“…As for the results of the study of Yahya and Abubakar (2012), when added protected methionine at different levels (0.2%, 0.4%/kg of dry matter) to the diets of fattening lambs where they noticed a significant increase in the average daily gain compared with the control group. Elwakeel et al (2018) did not record significant differences in the average daily gain when fed Barki lambs on diets contain 3g of protected lysine. Also, Abdelrahm (2010) did not find significant differences in the average total gain when fed Baladi goat breed on protected methionine (0, 2.5, 5) g/head/day.…”
Section: Resultsmentioning
confidence: 69%